Mitigating Cone Chute Telescopic Failures in Clinker Distribution Through Abrasion-Resistant Design Improvements - Jalil, Abdul; Saferi, Rozi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2024)
The cement industry plays a crucial role in supporting infrastructure development, making the smooth distribution of raw materials such as clinker essential for production efficiency. PT Semen Padang, a subsidiary of Semen Indonesia Group, produces clinker as a key intermediate material in cement manufacturing. One of the critical components in clinker distribution is the shiploader, responsible for transferring clinker from silos to the ship’s hold. However, frequent damage to the Cone Chute Telescopic component disrupts operations, increasing downtime and maintenance costs. This study aims to identify the root causes of Cone Chute Telescopic failures, propose durable design improvements, and develop applicable repair methods. A quantitative approach was employed through field observations and experimental analysis, focusing on the impact of clinker’s abrasive properties, high temperatures, and operational factors on component wear. A key solution implemented was the application of ceramic coating and 3mm steel plate lining to enhance resistance against abrasion. The study also explored the effects of cooling clinker before loading, optimizing chute design to reduce localized wear, and improving material selection for enhanced durability. Results indicate that clinker’s abrasive nature and high temperature significantly accelerate wear, particularly when ceramic coatings detach, exposing the fiber-reinforced material underneath. Additionally, structural issues such as inadequate suspension mechanisms and sensor malfunctions contribute to operational inefficiencies. The implementation of protective steel lining demonstrated a reduction in wear rates, suggesting a viable solution for extending component lifespan. The findings contribute to improving clinker distribution efficiency at PT Semen Padang and provide insights for the broader cement industry in enhancing the reliability of shiploading systems. Future research should focus on advanced composite materials and alternative cooling techniques to further mitigate clinker-induced wear.